KEDUDUKAN DEKLARASI UNIVERSAL HAK ASASI MANUSIA (UDHR) DALAM SISTEM HUKUM DI INDONESIA - Sinombor, Sonya Hellen (AL WASATH Jurnal Ilmu Hukum, 2022)
This paper analyzed the use of the Universal Declaration of Human Rights in Indonesia legal system. The research conducted through examining UDHR within Indonesian legal documents such as act (undang-undang), parliament decree (Tap MPR), and the decision of Constitutional Courts. This paper found that UDHR is being used in various ways. In some practice, it is stipulated in the considerans/preamble, contained in the article, in the explanatory section, and or as the attachment of the act/decree. In the Constitutional Court decision, the UDHR is used at least in two ways: as the backbone of the argument or as the supplement of the argument. This paper concluded that while the use of UDHR in Indonesia legal system may vary, but it at least signify the existence of the UDHR which should no longer be considered as â€œsoft lawâ€.